The challenge of managing ischemic stroke in brucellosis: a case report - Chen, Linfa; Lin, Xiaolong; Cai, Xiuqu; Zeng, Shiting; Yuan, Yanquan; Huang, Zhiyong; Yan, Jinjin; Li, You (Frontiers in Immunology, 2024)
A 64-year-old woman was admitted to the hospital for sudden weakness in one of her left limbs. The patient was diagnosed with acute ischemic stroke (IS) of undetermined cause and received intravenous thrombolysis. Following thrombolysis, the patient’s left limb weakness improved, but she subsequently developed recurrent high fever and delirium. Further diagnostic tests revealed that she had been infected with Brucella melitensis. The patient showed significant improvement during anti-infection treatment for Brucellosis and secondary prevention treatment for IS. However, her condition unexpectedly worsened on the 44th day after admission due to a hemorrhagic stroke (HS), which required an urgent craniotomy. Immunohistochemical analysis of the hematoma sample collected during the operation showed the presence of CD4+ and CD8+ T lymphocytes surrounding the blood vessels. This case highlights the unique challenge of managing IS in brucellosis and sheds light on the potential role of T lymphocytes in the immune response related to stroke.